Now I am presenting some algebraic formulae,
which are very commonly used and very useful for some special simplification
questions.
·
(a+b)2
= a2 + b2 + 2ab --------------------- (Equation no. 1)
·
(a-b)2
= a2 + b2 - 2ab --------------------- (Equation no. 2).
From
Equation 1 & 2
·
(a+b)2
+ (a-b)2 = 2 (a2 + b2)
·
(a+b)2
- (a-b)2 = 4ab --------------------- (Equation no. 3)
From
Equation 3
·
(a+b)2
= (a-b)2 + 4ab
·
(a-b)2
= (a+b)2 - 4ab
Other
Formulae
·
a2
- b2 = (a+b) (a-b)
·
(a+b)3
= a3 + b3 + 3ab (a+b) = a3 + 3a2b +
3ab2 + b3
·
(a-b)3
= a3 - b3 - 3ab (a-b) = a3 - 3a2b +
3ab2 - b3
·
(a3
+ b3) = (a+b) (a2 + b2 - ab)
·
(a3
- b3) = (a-b) (a2 + b2 + ab)
·
(a+
b+ c)2 = a2 + b2 + c2 + 2 (ab + bc +
ca) = a2 + b2 + c2 + 2ab + 2bc + 2ca
·
a3
+ b3 + c3 – 3abc = (a +b +c) (a2 + b2
+ c2 – ab – bc – ca)
=
(a+b +c) [(a-b)2 + (b-c)2
+ (c-a)2]
if a+ b+ c = 0
then a3 + b3 + c3
= 3abc
No comments:
Post a Comment